(untitled) (New Delhi, 1989)
The folklores and folktales have been an eternal part of every culture since ages. When it comes to Indian folk tales, the country of diverse religions, languages and cultures has a complete range of tales and short stories. Indian folklore has a wide range of stories and mythological legends, which emerge from all walks of life.
Keywords: Folk literature,Children's stories,Văn học dân gian,Chuyện của trẻ em; India,Ấn Độ